Integrating Natural Semantic Metalanguage (NSM) Theory in Developing E-Thesaurus of Semantic Primitives (English–Acehnese): Need Analysis Approach - Maria Ulfa; Purwati Purwati; Baihaqi Baihaqi; Siska Eka Syafitri (Journal of Educational Studies, 2026)
Semantic misinterpretation often occurs when translating between English and Acehnese due to cultural and linguistic differences. Conventional dictionaries usually provide direct lexical equivalents without adequately clarifying core meanings. Natural Semantic Metalanguage (NSM) offers semantic primitives, universal concepts shared across languages, that can serve as a basis for developing more accurate and culturally sensitive resources. This study applies NSM theory in the development of an English–Acehnese E-Thesaurus of semantic primitives, aiming to minimize misinterpretation and strengthen cross-cultural understanding. Using a qualitative design, semantic primitives were identified in English and matched with Acehnese equivalents through linguistic elicitation, textual analysis, and expert consultation. The results were organized into an E-Thesaurus prototype with a user-friendly digital interface to facilitate bilingual access. Findings show that NSM-based explications provide clearer representations of universal meanings while accommodating cultural nuances in both languages. The prototype demonstrates its potential as a tool for reducing ambiguity, enhancing bilingual learning, and promoting cultural literacy. Preliminary user feedback indicates that it improves comprehension of abstract concepts and minimizes translation errors. In conclusion, integrating NSM theory in the English–Acehnese E-Thesaurus offers an effective model to address semantic misinterpretation. Beyond bilingual education, this innovation contributes to cultural preservation and the promotion of cross-cultural communication.